When Financial Literacy is Not Enough: Assessing the Mediating Roles of Self-Efficacy and Behavior on Financial Well-being in Malang City - Hendra Suharjana; Umu Khouroh; Harmono Harmono (Innovation Business Management and Accounting Journal, 2026)
This study investigates the determinants of financial well-being among the residents of Malang City, specifically examining the mediating roles of financial self-efficacy and financial behavior. Using an explanatory research design with a quantitative approach, data were collected via structured questionnaires from 150 respondents across three generational cohorts (X, Y, and Z). The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results reveal that while financial literacy significantly strengthens both financial self-efficacy and financial behavior, it does not exert a direct impact on financial well-being. Notably, financial behavior also failed to act as a significant mediator in this relationship. Instead, financial self-efficacy emerged as a potent full mediator and the most critical predictor of financial welfare. These findings suggest that in a dynamic urban economy, technical knowledge and routine habits are insufficient without the psychological confidence to manage personal finances. To achieve holistic financial well-being, policymakers should shift from basic literacy programs to psychological empowerment initiatives that build inner conviction and mental resilience. This research highlights that the "psychological bridge" is far more essential than the "behavioral bridge" in translating knowledge into a secure financial future.